2001
DOI: 10.1046/j.1365-2133.2001.04462.x
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic quandary of hereditary haemorrhagic telangiectasia vs. CREST syndrome.

Abstract: The distribution and clinical appearance of the telangiectasia in the CREST syndrome (calcinosis, Raynaud's phenomenon, oesophageal involvement, sclerodactyly, telangiectasia) and hereditary haemorrhagic telangiectasia (HHT) are very similar. Several previously reported cases of the CREST syndrome simulating HHT illustrate this diagnostic quandary. We report a patient who met the diagnostic criteria for both the CREST syndrome and HHT, and discuss the distinguishing features of the two diseases, including the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
0
2
0
3
Order By: Relevance
“…It has been suggested that anticentromere antibodies can distinguish limited SSc from HHT ( 33 ). However, there are case reports where this is not the circumstance and distinguishing between limited SSc and HHT may present a diagnostic dilemma ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that anticentromere antibodies can distinguish limited SSc from HHT ( 33 ). However, there are case reports where this is not the circumstance and distinguishing between limited SSc and HHT may present a diagnostic dilemma ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Daha çok parmaklarda, yüzde, dudaklarda, ağızda ve gövde üst yarısında saptanır (3,5). Telenjiektaziler herediter hemorajik telenjiektaziyi (HHT) taklit edebilirler ve şiddetli kanamaya sebep olabilirler (9,10). Hastamızın yüzünde ve ellerinin üze-rinde telenjiektaziler mevcuttu.…”
Section: Discussionunclassified
“…Una complicación infrecuente, pero que se debe considerar, es la presencia de telangectasias en el estómago y el intestino, que pueden provocar sangrado digestivo (7,9) .…”
Section: Manifestaciones Gastrointestinalesunclassified
“…Las telangectasias aunque no son exclusivas de esta patología, son ampliamente asociadas al CREST, cuando se acompañan de Raynaud, Calcinosis, Esclerodactilia (9,22,24) .…”
unclassified